Implikasinya Pendidikan Karakter Peserta Didik Dalam Q.S Al Hujurat Ayat 1-5 Menurut Tafsir Ibnu Katsir - Pratama, Andy Riski; Charles, Charles (Alifbata : Jurnal Pendidikan Dasar, 2023)
Morals that hit some students in the country. One indicator of the crisis is due to the widespread coverage in the mass media related to impolite behavior by students in a number of educational institutions in the country, this issue shows that the practice of moral attitudes for students is very important in Islamic education. Therefore students must have good attitudes or morals towards educators, with a good attitude possessed by students and educators it is hoped that the goals of Islamic education can be achieved properly. The focus of the problem in this study is how students interact with educators in Q.S al-Hujurat verses 1-5 and their implications for Islamic education. The approach used in this study is library research (literature study), namely deepening, reviewing and identifying existing knowledge in the literature (reference books or other research results) related to the discussion under study. In this discussion the method used is the deductive method. From the results that the authors have done, it shows that the morals of students and educators have a polite attitude as contained in the contents of Al-Hujurat verses 1-5, that is, students may not precede when walking with educators, except for asking permission, when we are talking to educators, we are not justified in speaking loudly as we are talking to our neighbors, but in a voice that is gentle and full of respect. The implication in Islamic education, the attitude that students should have in interacting with educators is to imitate what has been explained by Allah in Q.S al-Hujurat verses 1-5, so with this all the rules regarding politeness will be applied in Islamic education.